A clinical study of prevalence of metabolic syndrome in psoriasis patients: a prospective cross-sectional observational study at a tertiary care centre in South India - R., Reshma; Manickam, Navakumar; Gopalan, Kannan; Kandasamy, Muthusamy (International Journal of Research in Dermatology, 2019)
Background: Metabolic syndrome (MS) is a constellation of risk factors like central obesity, atherogenic dyslipidemia, hypertension and glucose intolerance.Psoriasis is associated with MS and this may be contributed by various inflammatory mediators like interleukin 6 and tumor necrosis factor α which are increased in psoriasis. Aim of the study is to assess the prevalence and risk factors associated with metabolic syndrome in psoriasis patients and to find association between metabolic syndrome and severity of psoriasis using PASI score. Methods: A hospital based prospective observational cross sectional study was conducted in Vinayaka Missions Medical College and Hospital, Salem over a period of one year (June 2017 – June 2018) involving 100 psoriasis patients, included based on the inclusion and exclusion criteria. Patients were analyzed based on a standard proforma and metabolic syndrome was diagnosed with the South Asian Modified National Cholesterol Education Program Adult Panel III (SAM- NCEP ATP III). Results: In the present study, prevalence of metabolic syndrome was 54%. The risk factors noted were female gender (p=0.015), nail involvement (p=0.249), joint involvement (p=0.007) and increasing PASI score (p=0.194).There was no significant association between type of psoriasis and metabolic syndrome. Among the different components of metabolic syndrome, majority of psoriasis patients were having raised fasting blood sugar. Conclusions: The occurrence of metabolic syndrome is high in Indian population. Therefore apart from getting treated for psoriasis, patients should be screened for components of MS and should be followed up regularly for onset of components of MS.